PENYEBAB RELAPSE (KEMBALI MEROKOK) PADA PEROKOK BERAT DITINJAU DARI HEALTH BELIEF MODEL - Winurini, Sulis (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
Smoking cessation is not a simple thing for smokers. Most of them realized smoking is danger for their health, therefore they intense to quit. Nevertheless, many of them can’t be succeed in oversteping the rehabilitation process and than relapse. This research explore rehabilitation problem experienced by heavy smokers who have more complex relapse experience rather than smokers with lower level. This research used cognition approach, that is Health Belief Model (HBM). To explore the problem deeply, qualitative method has been used. The result is, although smokers have been through rehabilitation process, they didn’t fully understood that smoke is danger for themselves. Internal factor is the most influenting factor, especially health motivation and locus of control. This factors influence their perception on health threat and their evaluation of health behavior. Government has significant role for a successful modification of healthy new behavior through regulations.